ALBITE DISSOLUTION KINETICS AS A FUNCTION OF DISTANCE FROM EQUILIBRIUM: IMPLICATIONS FOR NATURAL FELDSPAR WEATHERING - Beig M.S.; Lüttge A. (My University, 2006)
Determining the kinetics of many geologic and engineering processes involving solid/fluid interactions requires a fundamental understanding of the Gibbs free energy dependency of the system. Currently, significant discrepancies seem to exist between kinetic datasets measured to determine the relationship between dissolution rate and Gibbs free energy. To identify the causes of these discrepancies, we have combined vertical scanning interferometry, atomic force microscopy, and scanning electron microscopy techniques to identify dissolution mechanisms and quantify dissolution rates of albite single crystals over a range of Gibbs free energy (-61.1 < ΔG < -10.2 kJ/mol). During our experiments, both a previously dissolved albite surface exhibiting etch pits and a pristine surface lacking dissolution features were dissolved simultaneously within a hydrothermal, flow-through reactor. Experimental results document an up to 2 orders of magnitude difference in dissolution rate between the differently pretreated surfaces, which are dominated by different dissolution mechanisms. The rate difference, which persists over a range of solution saturation state, indicates that the dissolution mechanisms obey different Gibbs free energy dependencies. We propose that this difference in rates is the direct consequence of a kinetic change in dissolution mechanism with deviation from equilibrium conditions. The existence of this kinetic "switch" indicates that a single, continuous function describing the relationship between dissolution rate and Gibbs free energy may be insufficient. Finally, we discuss some of the potential consequences of our findings on albite's weathering rates with a particular focus on the sample's history. © 2005 Elsevier Inc. All rights reserved.